2011
DOI: 10.1108/02640471111187999
|View full text |Cite
|
Sign up to set email alerts
|

Scholarly communication and possible changes in the context of social media

Abstract: PurposeThe focus of this paper is to study the influence of social media on scholarly communication. The aim is to provide an overview of researchers' use of Web 2.0 techniques, and discuss a possible change of information behaviors in the context of scholarly communication.Design/methodology/approachA web survey was distributed to a targeted sample of university staff (professors, teachers, researchers, and doctoral students). SPSS was utilized as a main tool to synthesize and analyze data, and present the re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
72
0
4

Year Published

2013
2013
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 107 publications
(79 citation statements)
references
References 25 publications
3
72
0
4
Order By: Relevance
“…Most fundamentally, Lupton (2014) has argued that these technologies also seem to have the potential to refashion scholarly communication by creating new forms of connection and new conversations. This was also observed by Gu and Widen-Wulff (2010) in their study of Finnish university staff's scholarly communication and how it is influenced by social media.…”
Section: Literature Reviewsupporting
confidence: 53%
“…Most fundamentally, Lupton (2014) has argued that these technologies also seem to have the potential to refashion scholarly communication by creating new forms of connection and new conversations. This was also observed by Gu and Widen-Wulff (2010) in their study of Finnish university staff's scholarly communication and how it is influenced by social media.…”
Section: Literature Reviewsupporting
confidence: 53%
“…The unifying term "Web 2.0" is closely related to the concept of social media. This term refers to technologies characterized as being user-centred, open, participatory, interactive and knowledge sharing (Gu and Widén-Wulff, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with Rowlands' results, they found that about one-third of researchers use social networks, falling short of wikis and blogs. Gu and Widén-Wulff (2011) also explored whether social media affect scholarly communication processes through a survey sent to researchers and employees at a Finnish university. Their results show that although most academics know about social networks, they use them much more in everyday life than in their research or teaching work.…”
Section: Introductionmentioning
confidence: 99%
“…There are 177 publications in this category (SCOPUS, 2016b). The topic that receive most attention in this category is related to the governance of DRR nationally (Bakkour et al, 2015;Chang Seng, 2013;Djalante et al, 2013;Guarnacci, 2012;Lassa, 2013). The next topic that receives greater attention is on the evaluation of recover and reconstruction that have taken place after the 2004 Indian Ocean 235 tsunami which hit Aceh, located in the Island of Sumatera (Chang et al, 2011;Daly and Brassard, 2011;Godavitarne et al, 2006;Guarnacci, 2012;Karan and Subbiah, 2011;Telford and Cosgrave, 2007).…”
Section: Disaster Risk Reduction 220mentioning
confidence: 99%